THE FORMING PEER EDUCATOR AND GIVING INFORMATION ABOUT REPRODUCTION HEALTH IN STUDENTS IN MA MASLAHATUL HIDAYAH IN ERRABU VILLAGE, KECAMATAN BLUTO - iva gamar dian pratiwi; Eko Mulyadi; Laylatul Hasanah (Jurnal ABDIRAJA, 2019)
MA Maslahatul Hidayah is a school located in Errabu Village, Bluto District. MA Maslahatul Hidayah is within the scope of the Maslahatul Hidayah boarding school. The number of students at MA Maslahatul Hidayah is 60 people. After the initial interview, it was found that most of the students did not understand about adolescent reproductive health including premarital sex, abortion, HIV / AIDS, sexually transmitted diseases, and in MA Maslahatul Hidayah there were no Peer Educators or peer groups that could be used as a container to tell and even provide counseling about reproductive health, especially in adolescents. Talking about reproductive health is considered a taboo by some students at MA Maslahatul Hidayah because they are in a boarding school environment, not only that there are some students who choose to drop out of school prematurely due to marriage under the age of 17 years. Culture and religion in Errabu Village are still quite thick and highly respected by the existence of this boarding school. The purpose of this PKM is to form a Peer Educator and increase students' Knowledge about Reproductive Health. The benefit of this activity is expected that with the existence of this PKM the knowledge of students about Reproductive Health will increase, so that the level of reproductive health of students increases. The method used is training and counseling. The results obtained are that this peer educator is very useful for MA Maslahatu Hidayah students, they are not awkward to consult with peer educators about the problems they face, especially regarding reproductive health and after counseling about reproductive health students become more understanding and understand the importance of maintaining reproduction health. Keywords: Peer Educator, Information, Reproductive Health, Adolescents.